STRATEGI NAFKAH MASYARAKAT DESA SINDANGSARI DI KAWASAN KAMPUS E UNTIRTA (Studi Kasus Desa Sindangsari, Kec. Pabuaran, Serang) - Euis kurniyawati; Nurul Hayat (Jurnal Pendidikan Sosiologi dan Humaniora, 2021)
The existence of Campus E UNTIRTA in Sindangsari Village certainly provides many  changes to the community. The impact of the existence of the E UNTIRTA campus giving a very visible change is a change in the economic situation of the surrounding population. This increase in income for the population is expected to have an impact, especially in the form of changes in the attitude of life of the population regarding the education of the people of Sindangsari Village. Of course, the existence of Campus E UNTIRTA will provide a source of income for the area around the campus to be an option for residents to fulfill their living needs and carry out livelihood strategies for their households. The research method applied is qualitative with descriptive method where this research will reveal cases and phenomena of the construction of the E UNTIRTA campus that affect the livelihood strategies of the community around the E UNTIRTA campus area as well as the socio-economic changes of the community which are revealed in depth to study the background, circumstances , and the interactions that occur. The purpose of this study was to analyze the Livelihood Strategy of the Sindangsari Village Community in the Campus E Untirta Area (Case Study of Sindangsari Village, Pabuaran District, Serang) which was just inaugurated by President Jokowi Dodo on Thursday, March 4, 2021 in Sindangsari Village, Pabuaran District, Serang District